WSS and MOSS 3.0 development (video training) : 10 solutions every SharePoint developer should know how to create - Hillier, Scot (LiveLessons., 2008)
"In this one-of-a-kind video package, Microsoft SharePoint MVP Scot Hillier walks you through building ten core SharePoint 2007 applications that every developer should know how to create. You'll master state-of-the-art SharePoint 2007 development through 11 quick video lessons covering both Windows SharePoint Services (WSS) and Microsoft Office SharePoint Server (MOSS). One step at a time, Hillier introduces SharePoint 2007's most powerful capabilities and shows exactly how to take advantage of them in your own applications. Just watch: You'll learn essential SharePoint techniques and best practices at your own pace--and get specific answers and solutions immediately, whenever you need them!"--Resource description page